Clopidogrel Resistance Is Associated With DNA Methylation of Genes From Whole Blood of Humans - Yang, Jin; Yu, Qinglin; Xu, Zhifeng; Zheng, Nan; Zhong, Jinyan; Li, Jiyi; Liu, Yahui; Xu, Hongyu; Su, Jia; Ji, Lindan; Chen, Xiaomin (Frontiers in Genetics, 2021)
Antiplatelet therapy has become a cornerstone in the treatment of coronary heart disease (CHD). However, due to high-residual-platelet-reactivity, clopidogrel resistance (CR) is a common phenomenon，and it is rarely known about the relationship between CR and epigenetic changes. This study compared the whole genomic methylation patterns of blood samples from patients with CR and controls with the Human Methylation 850 K BeadChip assay. We explored differentially methylated CpG sites, genes, and pathways using bioinformatics profiling. The CR and control groups showed significantly different DNA methylation at 7098 sites, with 979 sites showing hypermethylation and 6119 sites showing hypomethylation. The pyrosequencing method was used to validate four differentially methylated CpG loci (cg23371584, cg15971518, cg04481923, cg22507406), confirming that DNA methylation was associated with the risk of CR. The relative mRNA expression of the four genes (BTG2, PRG2, VTRNA2-1, PER3) corresponding to the loci above was also associated with CR , suggesting that alterations in DNA methylation may affect the expression of these four genes, eventually resulting in CR. Additionally, differentially methylated sites are partially related to genes and pathways that play key roles in process of circadian entrainment, insulin secretion, and so on. Hence, the mechanism and biological regulation of clopidogrel resistance might be reflected through these epigenetic alterations, but future research will need to address the causal relationships.